Design, synthesis, and in vitro evaluation of aza-peptide aldehydes and ketones as novel and selective protease inhibitors - Corrigan, Thomas S; Lotti Diaz, Leilani M; Border, Sarah E; Ratigan, Steven C; Kasper, Kayla Q; Sojka, Daniel; Fajtova, Pavla; Caffrey, Conor R; Salvesen, Guy S; McElroy, Craig A; Hadad, Christopher M; Doğan Ekici, Özlem (Journal of enzyme inhibition and medicinal chemistry, 2020)
Aza-peptide aldehydes and ketones are a new class of reversible protease inhibitors that are specific for the proteasome and clan CD cysteine proteases. We designed and synthesised aza-Leu derivatives that were specific for the chymotrypsin-like active site of the proteasome, aza-Asp derivatives that were effective inhibitors of caspases-3 and -6, and aza-Asn derivatives that inhibited S. mansoni and I. ricinus legumains. The crystal structure of caspase-3 in complex with our caspase-specific aza-peptide methyl ketone inhibitor with an aza-Asp residue at P1 revealed a covalent linkage between the inhibitor carbonyl carbon and the active site cysteinyl sulphur. Aza-peptide aldehydes and ketones showed no cross-reactivity towards cathepsin B or chymotrypsin. The initial in vitro selectivity of these inhibitors makes them suitable candidates for further development into therapeutic agents to potentially treat multiple myeloma, neurodegenerative diseases, and parasitic infections.
Keywords: Cattle; Animals; skot; vztah mezi dávkou a účinkem léčiva; anticancer; aza sloučeniny; Aza Compounds; Protease Inhibitors; Molecular Structure; aza-peptide carbonyls; Structure-Activity Relationship; lidé; inhibitory proteas; Ketones; krystalografie rentgenová; caspase and legumain inhibitors; antiparasitic; Aldehydes; Models, Molecular; molekulární struktura; peptidy; aldehydy; Dose-Response Relationship, Drug; cysteinové endopeptidasy; molekulární modely; proteasomový endopeptidasový komplex; racionální návrh léčiv; Cysteine Endopeptidases; ketony; Drug Design; vztahy mezi strukturou a aktivitou; zvířata; Crystallography, X-Ray; Proteasome inhibitor; Peptides; Proteasome Endopeptidase Complex; Humans